APPLICATION OF MATERIAL FLOW ANALYSIS (MFA) ON BIOVALORIZATION SYSTEM OF SOY SAUCE AND TOFU SOLID WASTE INTO SEASONING SAUCE PRODUCTS - Fediyani, Hanif Faizah Eka; Hendrasarie, Novirina; Rosida, Dedin Finatsiyatull; Larasati, Sekar Ayu (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2026)
The massive volume of agroindustrial solid waste from soy sauce (59.7%) and tofu (35.5%) production has the potential to pollute the environment if it ends up in water bodies. However, the high nutrient content opens up opportunities for biovalorization into value-added products. Soy sauce solid waste has a protein content of 16.31%, and tofu solid waste has a protein content of 4.78%. This study aims to produce a plant-based sauce from soy sauce and tofu residues by adding banana peel pectin as a thickener, while simultaneously calculating the waste reduction rate using Material Flow Analysis (MFA) with STAN 2.7.101 software. The method used was solid-state fermentation (SSF) for 72 hours using Aspergillus oryzae and Aspergillus sojae. The sauce characteristics were evaluated through pH, protein content, and organoleptic testing using a scoring method (1–5) to determine the best treatment. From the MFA mapping, it was proven that the biovalorization process of soy sauce residue-based sauce was able to reduce solid waste by up to 55.14%, which is more efficient compared to tofu residue, which only reduced waste by 44.51%.